Pengaruh Return On Assets, Return On Equity Dan Current Ratio Terhadap Pertumbuhan Laba Pada Perusahaan Sektor Perdagangan Eceran yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022 - Sindiani Fatimah; Siska Widia Obaita; Hari Sulistiyo (Jurnal Ilmiah Wahana Pendidikan, 2023)
Management can use profit growth as a growth ratio to measure company performance, because profit growth reflects management's success in managing the company effectively and efficiently. The purpose of this research is to test and analyze the effectReturn On Assets, Return On Equity Dan Current Ratio to Profit Growth. The approach in this study uses quantitative methods. The population in this study are 35 retail trade sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period using the purposive sampling obtained from 32 samples. The test method used is multiple linear regression analysis. The results of the study show that ROA and ROE have an effect on profit growth. While CR has no effect on profit growth. The f test calculation is obtainedReturn On Assets, Return On Equity Dan Current The ratio simultaneously influences the profit growth of retail trading companies on the Indonesia Stock Exchange.